2007
DOI: 10.2190/ec.37.4.c
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Effectiveness of Note Taking on Computer-Based Graphic Organizers

Abstract: Previous research on graphic organizer (GO) note taking has shown that this method is most effective when the GO is presented to the student partially complete with provided notes. This study extended prior research by investigating the effects of provided note type (summary vs. verbatim) and GO bite size (large vs. small) on the transfer performance and note taking behavior of college students working with a set of partially complete computer-based GOs. As hypothesized, a note-type by bite size interaction oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(85 reference statements)
0
10
1
Order By: Relevance
“…Many of these studies predate the rapid advancement of educational technology and the increasing use of computers in science education ( Higgins & Spitulnik, 2008 ) and instead focus on the analysis of paper-based note-taking (e.g., Weiss et al, 2001 ). As more and more learning is happening through computer-based learning environments, researchers have begun to investigate the effects that computers have on students’ note-taking strategies and learning (e.g., Bauer and Koedinger, 2006 , Bui et al, 2013 , Crooks et al, 2007 , Igo et al, 2005 , McQuiggan et al, 2008 , Mueller and Oppenheimer, 2014 , Robinson et al, 2006 ). However, no study we are aware of has systematically and comprehensively investigated note-taking in science open-ended learning environments (OELEs) for middle school learners.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies predate the rapid advancement of educational technology and the increasing use of computers in science education ( Higgins & Spitulnik, 2008 ) and instead focus on the analysis of paper-based note-taking (e.g., Weiss et al, 2001 ). As more and more learning is happening through computer-based learning environments, researchers have begun to investigate the effects that computers have on students’ note-taking strategies and learning (e.g., Bauer and Koedinger, 2006 , Bui et al, 2013 , Crooks et al, 2007 , Igo et al, 2005 , McQuiggan et al, 2008 , Mueller and Oppenheimer, 2014 , Robinson et al, 2006 ). However, no study we are aware of has systematically and comprehensively investigated note-taking in science open-ended learning environments (OELEs) for middle school learners.…”
Section: Introductionmentioning
confidence: 99%
“…All three studies favored requiring users to compose a response (fill-in-the-blank) rather than select a response (multiple choice). One study compared the effects of requiring users to compose original note summaries versus requiring users to copy and paste text to create notes while using large and small graphical organizers (Crooks, White, & Barnard, 2007). This study found no significant main effects between conditions, although a significant interaction was found.…”
Section: Response Requirementsmentioning
confidence: 89%
“…However, graphic organizers were not only used in reading comprehension (Kim et al, 2001) but they have been also used in many different lines of research such as scientific research (Rulea, Baldwin & Schell, 2008), web-based research (Crooks, White & Barnard, 2007), note taking with both print-based (Robinson et al, 2006), and computerbased instruction (Katayama & Grooks, 2003;Katayama, Shambaugh, & Tasneem, 2005). Furthermore, diagrams facilitate and organize thinking.…”
Section: Graphic Organizers and Educational Researchmentioning
confidence: 99%
“…Graphic organizers can also facilitate managing cognitive load by lightening the working memory demands and freeing up space to focus on the requirements of a task rather than investing efforts for understanding the content of the text (e.g. Crooks, White & Barnard, 2007;Larkin & Simon, 1987;Stull & Mayer, 2007). Graphic organizers may help relational learning and integrated writing (Robinson & Kiewra,1995), allowing students to learn relations easily (Robinson & Schraw, 1994) and helping effective processing of relational information (Bera & Robinson, 2004).…”
Section: Argumentation Diagramsmentioning
confidence: 99%
See 1 more Smart Citation